NF1 loss induces senescence during human melanocyte differentiation in an iPSC‐based model. (22nd April 2015) - Larribere, Lionel; Wu, Huizi; Novak, Daniel; Galach, Marta; Bernhardt, Mathias; Orouji, Elias; Weina, Kasia; Knappe, Nathalie; Sachpekidis, Christos; Umansky, Ludmila; Beckhove, Philipp; Umansky, Viktor; et al.
Summary Neurofibromatosis type 1 (NF1) is a frequent genetic disease leading to the development of Schwann cell‐derived neurofibromas or melanocytic lesions called café‐au‐lait macules (CALMs). The molecular mechanisms involved in CALMs formation remain largely unknown. In this report, we show for the first time pathophysiological mechanisms of abnormal melanocyte differentiation in a human NF1+/−‐induced pluripotent stem cell (iPSC)‐based model. We demonstrate that NF1 patient‐derived fibroblasts can be successfully reprogrammed in NF1+/− iPSCs with active RAS signaling and that NF1 loss induces senescence during melanocyte differentiation as well as in patient's‐derived CALMs, revealing a new role for NF1 in the melanocyte lineage.